Factors Controlling the Spatial Distribution of Dissolved Organic Matter With Changes in the C/N Ratio From the Upper to Lower Reaches of the Ishikari River, Japan - Takaki, Yuji; Hattori, Keisuke; Yamashita, Youhei (Frontiers in Earth Science, 2022)
Dissolved organic matter (DOM), particularly dissolved organic nitrogen (DON), is an important source of energy and/or organic nutrients for heterotrophic microorganisms in rivers. Although various factors controlling the quantity and quality of stream and riverine DOM have been extensively studied, DON has been under-researched compared to dissolved organic carbon (DOC). The spatial distribution of DOC and DON concentrations with respect to the C/N ratio and DOM optical properties was investigated in the Ishikari River and its tributaries in Hokkaido, northern Japan. Here, the upper reaches are forested and the middle and lower reaches are encompassed by agricultural land, in particular paddy fields. Furthermore, dark incubation experiments were conducted using filtered riverine water (<0.7 µm) to determine the bioavailability of DOC and DON (particularly due to small microorganisms) considered as a factor controlling the spatial distribution. In the mainstream, DOC and DON concentrations increased with river flow in the upper and middle reaches and remained unchanged in the lower reaches. The C/N ratio of bulk DOM decreased continuously from the upper reaches to lower reaches. The optical properties exhibited changes in the DOM characteristics in terms of higher molecular weight and higher aromaticity from the upper to middle reaches, suggesting that flooded paddy fields largely altered the riverine DOM concentration and composition. In the lower reaches, the C/N ratio of the bulk DOM decreased with the river flow. However, according to principal component analysis, no changes were observed in the optical properties with river flow, suggesting that the C/N ratio of bulk DOM changed owing to in situ biological activity in the river. DOC biodegradation was observed at four sites in the upper and middle reaches but not at the two sites in the lower reaches. However, the DON concentration during the dark incubation experiments at all sites did not differ significantly, which implies that microbial degradation, particularly by small microorganisms, is a factor that decreased the C/N ratio of bulk DOM in the upper and middle reaches. In contrast, large microorganisms possibly degraded C-rich DOM to decrease the C/N ratio of bulk DOM in the lower reaches of the Ishikari River.